Vaccination as an intervention against Escherichia coli O157:H7 in cattle feces - Choat, William Travis, author; Belk, Keith E., advisor; Paterson, John A., advisor; Smith, Gary C., committee member; Engle, Terry E., committee member; Umberger, Wendy J., committee member (Colorado State University. Libraries, 2006)
Three hundred sixty-seven recently weaned steers were used in a growing (45 d) and finishing (189 d) experiment to determine if vaccination with an experimental E. coli O157:H7 vaccine would reduce fecal shedding and elevate antibody titers. Treatments (TRT) compared were: Group 1) received two doses of the E. coli vaccine in the growing phase only; Group 2) received two doses of the E. coli vaccine during the growing phase and a third dose on d 100 of the finishing phase; Group 3) received two doses of the E. coli vaccine; one on d 21 of the finishing phase and a second dose on d 100 of the finishing phase. Treatment group 4 served as the control (no vaccination). On d 0 and 45 of the growing phase and d 21, 100 and 162 of the finishing phase, fecal grab and venous blood samples were collected. Fecal samples were analyzed for E. coli O157:H7 by Food Safety Net Services. Blood samples were sent to Fort Dodge Laboratories for analysis of antibody titers against E. coli O157:H7. Prevalence of fecal E. coli O157:H7 was not different (P > 0.05) at any sampling period among treatment groups. The initial and final prevalence rates during the feedlot phase for TRT 1 were one and 10%; TRT 2 were 3 and 8%; TRT 3 were 3 and 17%, and TRT 4 (Control) were 5 and 8%, respectively. Serum titers showed elevated immune response, during the 45 d growing phase, vaccine increased (P < 0.001) blood titers from an average of 62, to 2,217. During the finishing period, vaccinated calves had higher titers compared to Control calves (avg. of Trt 1, 2, 3 vs. TRT 4 (P < 0.05). Vaccination during the 45 d growing phase, and then again on d 100 of the finishing phase (TRT 2), resulted in the greatest (P = 0.012) pre-slaughter titer level, but did not affect (P > 0.05) E. coli O157:H7 prevalence. At harvest, TRT 1 steers' titer levels had returned to near pre-vaccination levels, indicating that immune levels declined over time. Although an immune response was generated by this vaccine, the limited number of animals shedding E. coli O157:H7 warrants additional research in calves with higher levels of shedding.
Keywords: food science